O investimento estrangeiro na URSS - Pomeranz, Lenina (1989)
This paper summarizes the first results of the soviet policy concerning the establishment of joint-ventures with foreign capital in the USSR through 1987-1988. The data utilized in the analysis is the roll of joint-ventures registered at the Ministry of Finances of the USSR.